How to Promote Halal Tourism through the Stakeholders? Case of Halal Tourism Market in Indonesia - Anniza Citra Prajasari (Jurnal Ilmiah Ekonomi Islam, 2022)
Inline to accelerate the development of halal tourism in Indonesia, this paper aims to analyze the halal tourism market in Indonesia through the approach of Muslim tourist behavior both in terms of current supply and potential demand. By using a combination method as a research approach, the results of this study are expected to be more contributive in formulating promotion strategies and development of halal tourism throughout Indonesia, especially in D.I. Yogyakarta. This study involved 718 respondents. This research was completed with interviews at the West Nusa Tenggara Province Culture and Tourism Office as a role model in the development of halal tourism. The results of the analysis show that tourists are dominated by the millennial generation and women, where differences in gender and age generations also indicate behavior and needs in traveling. In the end, there are at least seven strategies that can be done to develop halal tourism, such as (1) regulations; (2) acceleration of halal certification; (3) optimization of supporting facilities and infrastructure; (4) cooperation with business actors and travel agents; (5) approaching religious and community leaders; (6) cooperation with airlines; and (7) actively involved in national and international promotion.